Time to treat the climate and nature crisis as one indivisible global health emergency - Kamran Abbasi; Parveen Ali; Virginia Barbour; Thomas Benfield; Kirsten Bibbins-Domingo; Stephen Hancocks; Richard Horton; Laurie Laybourn-Langton; Robert Mash; Peush Sahni; Wadeia Mohammad Sharief; Abdullah Shehab; et al. (Caribbean Medical Journal, 2024)
Over 200 health journals call on the United Nations, political leaders, and health professionals to recognise that climate change and biodiversity loss are one indivisible crisis and must be tackled together to preserve health and avoid catastrophe. This overall environmental crisis is now so severe as to be a global health emergency.